Generic Digital Forensic Business Model – Malaysian Case Study (International Journal of Innovative Computing, 2018)
Rapid development of cyberspace has created a healthy competition in the creation of computer systems and other devices. The impact of these developments is that cyber threats had caused hectic in digital security area and its reliability to be the trusted system in the industry. Therefore, in order resolve the problem, many countries began developing their own procedures for investigating cyber-related cases based on their own law and regulations and it when the term of digital forensic take place. Researchers began to provide the best definition of each potential element that said as can be a structure in the digital forensic. On other part, the preparations of designing the investigation procedures were based on various designs. In this research, modified investigative procedures are centered on the Malaysian Chief Government Security Office (MCGSO) as a central authority providing advisory services in the field of physical security, document security, personnel security and ICT security. The comparison between approaches had been made where it cover two (2) approaches namely framework and business model. Based on the survey that been made within the organization, selection of design and framework for digital forensic for this organization is based on the business model in general and the Digital Forensic Business Model in particular and it will link together with the general elements and components of digital forensic.